Microsoft XNA Game Studio 3.0 unleashed - Carter, Chad (Unleashed., 2009)
Using XNA Game Studio 3.0, any programmer can master the art of game development and begin selling games to millions of Xbox 360 users worldwide. Now, there's a practical, comprehensive guide to game development with Microsoft's powerful new XNA Game Studio 3.0 and the entire XNA Framework. In Microsoft® XNA® Game Studio 3.0 Unleashed, XNA expert Chad Carter covers the entire XNA platform, presents extensive sample code, and explains that code line by line. Carter walks you through the entire process of game development, including installing XNA, creating objects, handling input, managing and extending the content pipeline, optimizing game performance, and creating both 3D and 2D games. Carter presents sophisticated coverage of using XNA's high level shader language; creating physical effects; and endowing characters with realistic artificial intelligence. A case study section walks through the entire process of planning and coding a game, improving it, and putting on the finishing touches that make it marketable. This edition contains nine new chapters, including all-new sections on creating networked games, programming games for the Zune handheld, and preparing and submitting games to Xbox LIVE, where accepted titles will reach gamers worldwide. Plan your games to deliver solid performance on the platforms you've targeted Understand essential XNA Framework concepts, including object creation, cameras, input handling, libraries, game services, and managing and extending the content pipeline Create a 2D game that will run across 3 platforms (Windows, Xbox 360, and Zune) with a single code base Create a Visualizer media player for the Microsoft Zune Use the High Level Shader Language (HLSL) to communicate directly with graphics hardware Bring realistic physics to your game action and realistic artificial intelligence to your characters Create sophisticated 3D effects that use advanced texturing and a particle system Build networked games, including multiplayer demos, turn-based games, and real-time network games Create 4 full games-2D parallax side scroller, 3D shooter, multiplayer turn-based 2D card game, and a multiplayer real-time 3D game Discover best practices for creating Xbox LIVE Community Games Sell your finished game on Xbox LIVE Marketplace CD-ROM includes: All C# examples and source code presented in this book.